Mediating Influence Of Self-Esteem On Relationship Between Ethical Leadership And Job Performance - Saragih, Masriani; Yustina, Andi Ina; Santosa, Setyarini (Jurnal Riset Akuntansi dan Keuangan, 2020)
Leaders with ethical leadership promote ethical conduct to their followers through two-way communication such as setting ethical standards and discipline for those who violate the standards. High ethical leadership of leaders within organizations will lead to a high level of employee self-esteem. Employees with high self-esteem will be more confident with their own behavior and attitudes. Thus, it will encourage them to give extra effort and maintain exemplary performance within the organizations. This research aims to examine the effect of ethical leadership toward employees’ job performance and the mediating role of self-esteem in these relationships. Data was collected using questionnaires with responses from 160 employees of 15 major industries in Indonesia. The results indicate that ethical leadership significantly and positively affects job performance, while the mediating role of self-esteem partially mediates the relationship of ethical leadership and job performance. This study also found that ethical leadership can affect employees’ job performance directly without mediating variables and the results are significantly positive.